Europejskie standardy swobody wypowiedzi a fenomen tabloidów – między obowiązkami a odpowiedzialnością - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper emphasizes that the European Court of Human Rights in Strasbourg has never differentiated standards of freedom of speech with regard to the medium used to present one’s views. The Court has thus vested the controlling function mass media can play both to the quality press and tabloids. On the other hand, however, the Court did not agree with a concept that was particularly strong in Polish journalism, that the red tops cannot be treated as seriously as the quality press. If this concept were to be accepted, the freedom, or rather irresponsibility, of the tabloid or sensational press addressed at a mass reader would be significantly larger than the field of freedom defined for the ‘serious’ mass media. Therefore, the sensational character of the press does not provide it with greater freedom, nor does it justify a more restrictive approach to its coverage.